Dynamics of the main types of scientific articles in the journal "theory and practice of physical culture" (1925-2022) - L.I. Lubysheva; S.S. Filippov; S.A. Pronin; M.V. Bagaev (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the features of the dynamics of the main types of scientific articles in the journal "Theory and Practice of Physical Culture". Methods and structure of the study. In the course of scientific work, a typology of publications, statistical observation, and systematization were carried out. The sample of scientific articles amounted to 21,388 items published in the journal TPPC for 1925-2022. Four periods were identified in the dynamics of quantitative indicators of publications. Results and conclusions. Dynamics of scientific articles published in 1925-2022 in the journal TPPC, has the following features: 1925-1965 characterized by a steady growth of scientific publications; 1966-1987 fix their consistently high number; 1988-2003 are distinguished by a pronounced decline in the number of scientific publications; 2004-2022 significant growth in the number of scientific articles. In addition, significant features of the dynamics of articles with a theoretical, descriptive and applied orientation are highlighted. It is noted that the low level of hardware for scientific research in the field of physical culture and sports is one of the main brakes on their development in modern conditions.